Earnings management by choosing between accounting options available in the IFRS: Presenting a sample of standards and their impact on the financial statements - talbi, ahmed zakaria; elorabi, Hameza (Journal of Research in Finance and Accounting, 2021)
The current paper aims to reveal how managers can use earnings management by using the flexibility of IFRS and the ability to choose between different accounting options to realize personal interests. The study conclude that the accounting result may be subject to intentional manipulation resulting from a lack of professional ethics of managers, what can decrease the quality of financial statements.